Copper(i) catalyzed synthesis of selanyl methylene 4-chromanol and aurone derivatives. Issue 24 (10th June 2020) - Sahoo, Sushree Ranjan; Sarkar, Debayan; Henkel, Felix; Reuter, Hans
Abstract : An efficient copper-catalyzed cyclization cascade approach towards highly functionalized methylene 4-chromanol and aurone derivatives has been developed from reactions of ynols via 6- exo-dig and 5- exo-dig cyclization respectively. Abstract : An efficient copper-catalyzed cyclization cascade approach towards highly functionalized methylene 4-chromanol and aurone derivatives has been developed from reactions of ynols via 6- exo-dig and 5- exo-dig cyclization respectively. The catalysis involves alkyne activation via diorgano-diselenides and also their regioselective incorporation into the methylene 4-chromanol and aurone derivative core and is an open-air transformation.